Impact of Treasury Single Account (TSA) on Public Sector Performance in Sierra Leone for the 2015-2022 - Emmanuel Jam Kamara; Alpha Kanu; James L.S. Kollie (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2023)
The study explores the impact of Treasury Single Account (TSA) on the performance of public sector in Sierra Leone. This study primarily examined the extent to which TSA has improved Government Collected Revenue (GCR) and Government Expenditure (GE) of the public sector. Secondary data that were sourced from the Ministry of Finance Sierra Leone were used for this research. The observations were recorded on yearly basis from 2015 to 2022. The data were divided into two periods: Pre TSA period (2015 to 2018) and Post TSA period (2019 to 2022). A pre-post analysis (difference in means test) was carried out using statistical package for social sciences version 25. The findings show that TSA implementation has a positive and significant effect on the revenue mobilization in Sierra Leone. However, further findings revealed that Government Expenditure (GE) significantly increased after the implementation of TSA. The study concludes that implementation of Treasury Single Account (TSA) has improved revenue generation in Sierra Leone. The study recommends that periodic appraisal of each revenue generating sector should be implemented so that some un-performing sectors are expose against the performing sectors.